Persepsi pelajar terhadap tahap keberkesanan kepimpinan pertubuhan majlis perwakilan palajar (MPP) di institusi pengajian tinggi awam (IPTA) : satu kajian kes di Universiti Malaysia Sarawak (UNIMAS) - Amelia, Anak Mun (Universiti Malaysia Sarawak (UNIMAS), 2001)
Generally this research aims to idenllfy the level of leadership e!fectivenc.fS of Student's Representative Council, (Majlis Perwakilan Pelajar(MPP) University Malaysia Sarawak) and factors that contribute to their effectiveness. Questionnaire method was used as an instrument to find the feedback from 76 respondents. Statistical Package for Social Sciences, Window-7.5 software was used to analyze the primary data. t-test method was used to identify the signtjicant of the mean differences between the respondent's perception according 10 their demographically factors such as sex, faculty and ltadership experiences. Multiple Pearson Correlation test was used to identifY the significant relationship of respondtnt~ perception toward the MPP leadership effectiveness level according to the student ltadership approaches on factors such as trait, behavior and communication skills. Unear Regression test was also used to identify the dominant factor that influence the effectiveness level of MPP leadership. The research's finding of showed that there is insignificant of mean differences between the two groups of every each demographically factors of the respondents, which the values are (t=0.182, P=0.856»0.05; (t=0.261, paO.795»0.05, and (1=1.085, P=0.281»0.05. This finding showed that the first, second and the third offUlli hypothesis in this research were accepted. Pearson Correlation Test 's findings showed that there are significant relationship between students perception toward MPP leadership effectivenes.f level according to all the factors, which the value.f of each factors is (r-O.852",P=O.OOO); (r=0.846··, P=O.OOO); and (r=0.802··, P=O.OOO). From tMt finding, tile null hypotheses of all the factors were rl!jected. Finally, thl! Linear Regression Test found tMt behavior af'proach of leadership is the dominant factor in tltis research witll tile value of R2=O.72.6 which contributed 72.6 % of overall respondent's perception.